Information and Analytical Support for the Management of Law Enforcement and Socio-Economic Activities (on the Basis of Methodologies and Practices of Applied Statistics) - Zakhozhai, V. B. (Statistics of Ukraine, 2023)
The article discusses the information and analytical aspect of the management in the three vitally important spheres of the human activities, i. e. social, economic and law enforcement ones, from the perspective of a comprehensive diagnostics of the circumstances and factors that have impact on their efficiency. The number of principles to be laid in the basis of a study devoted to the information and analytical support (IAS) of the law enforcement system are proposed. The results of this study show that IAS, apart from using advanced information technologies, provides a framework for substantiating and elaborating the measures aimed at the elimination of actual and potential crime as a threat to the successful social and economic development of a country, correcting the goals, objectives and directions of combatting the crime in keeping with the needs of the social and economic activities, rational selection of the staff and their effective use, etc. The implementation of the outlined objectives involves the emphasis on keeping with the requirements of the legal support for the national and economic security of the state. The following components of the diagnostics were defined: identifying the problem’s essence; constructing a set of indicators; creating a methodological framework for the assessment of proportionality, intensity and tendency of the development, the causality and effectiveness of the structural transformation; ranking the effectiveness of activities; assessing in real time the consequences of the implemented administrative decisions; controlling the execution of elaborated measures on combatting crime, etc. The methodology of statistical study, establishing the rules, techniques and methods for defining the patterns and tendencies of socio-economic phenomena and processes under the impact of factors originating from the internal and external environment, is proposed as the key component of the diagnostics. The law enforcement bodies are characterized in the context of study of social and economic problems as not only a penitentiary institution, but also the one which work is backed by analysis and preventive forecasting of violations and their factors and involves recommendations on their prevention. It is demonstrated that the management in combatting crime is a complex activity aimed at the achievement of positive results through the effective utilization of available resources and the implementation of principles, functions and methods of analytical study. The effective combatting of crime has to rest upon the comprehensive monitoring, which is a multitier system for tracing and predicting the dynamics of socio-economic processes by use of advanced tools of politics, surveillance and reaction. These objectives have to be achieved by IAS system enabling for causal links between law enforcement and socio-economic activities, which components are proposed in the article. Its result is a statistical assessment of these processes in their causality with management objectives, laying the basis for making creative management decisions.